Prospects for utilisation of non-vacancy Internet data in labour market analysis: An overview - Karolien Lenaerts; Miroslav Beblavý; Brian Fabo (IZA Journal of Labor Economics, 2016)
Along with the advancement of the Internet in the last decade, researchers have increasingly identified the web as a research platform and a data source, pointing out its value for labour market analysis. This article presents a review of online data sources for this field. Specifically, the article introduces web-based research, focusing on the potential of relatively new data sources such as Google Trends, social networks (LinkedIn, Facebook and Twitter) and Glassdoor (surveys). For these data sources, a review is done and recent empirical applications are listed. Web-based data can further our understanding of the dynamics of the labour market.
Keywords: E4; J2; 330; Labour market; Web-based research; Data sources; Google Trends; Social networking sites; Glassdoor